Differences Sustained Between Diffuse and Limited Forms of Juvenile Systemic Sclerosis in an Expanded International Cohort. Issue 10 (8th June 2022) - Foeldvari, Ivan; Klotsche, Jens; Kasapcopur, Ozgur; Adrovic, Amra; Terreri, Maria Teresa; Sakamoto, Ana Paula; Stanevicha, Valda; Sztajnbok, Flavio; Anton, Jordi; Feldman, Brian; Alexeeva, Ekaterina; Katsicas, Maria; et al.
Abstract : Objective: To evaluate the baseline clinical characteristics of juvenile systemic sclerosis (SSc) patients in the international juvenile SSc inception cohort, and to compare these characteristics between the classically defined juvenile diffuse cutaneous SSc (dcSSc) and limited cutaneous SSc (lcSSc) subtypes and among those with overlap features. Methods: A cross‐sectional study was performed using baseline visit data. Information on demographic characteristics, organ system evaluation, treatment, and patient‐ and physician‐reported outcomes was extracted and summary statistics applied. Comparisons between juvenile dcSSc and lcSSc subtypes and patients with and without overlap features were performed using chi‐square and Mann‐Whitney U tests. Results: At data extraction, 150 juvenile SSc patients were enrolled across 42 centers; 83% were White, 80% were female, juvenile dcSSc predominated (72%), and 17% of the cohort had overlap features. Significant differences were found between juvenile dcSSc and juvenile lcSSc regarding modified Rodnan skin thickness score, the presence of Gottron's papules, digital tip ulceration, results of the 6‐minute walk test, and composite pulmonary and cardiac involvement. All of these were more frequent in dcSSc except for cardiac involvement. Juvenile dcSSc patients had significantly worse scores for physician‐rated disease activity and damage. A significantly higher occurrence of Gottron's papules and musculoskeletal and composite pulmonary involvement, and a significantly lower frequency of Raynaud's phenomenon, were seen in those with overlap features. Conclusion: Results from a large international juvenile SSc cohort demonstrate significant differences between juvenile dcSSc and juvenile lcSSc patients, including more globally severe disease and increased frequency of interstitial lung disease in juvenile dcSSc patients, while those with lcSSc have more frequent cardiac involvement. Those with overlap features had an unexpected higher frequency of interstitial lung disease.